Techno-economic analysis of potential natural gas liquid (NGL) recovery processes under variations of feed compositions - Woldetensay, Mesfin; Mhadazir, S.; Long, N.; Lee, M. (Elsevier, 2013)
This paper presents the different process schemes used for known NGL recovery methods with respect to their economic performance. The original turbo-expander (ISS) was considered as base case plant. The GSP, CRR and RSV process schemes focus on improvement at the top of the demethanizer column. The IPSI-1 and IPSI-2 schemes focus on the bottom of the demethanizer column. All the process schemes were initially built using Aspen HYSYS with a common set of operating criteria. Numerous simulation runs were made by taking various typical feed compositions classified as lean and rich. The economic assessment for each process scheme was later made by considering the capital cost, operating cost and profitability analysis. Results showed that the IPSI-1 process scheme gives the best economic performance with lowest TAC and payback time compared to the other process schemes. On the other hand, the RSV process gives higher TAC and payback time compared to others.